Implementasi Putusan Hakim pada Perkara No.148/Pdt.G/2024/Pn Tab.Sengketa Tanah di Desa Antapan Kabupaten Tabanan - Wayan Agus Kertiyasa; I Made Mulyawan Subawa; Ida I Dewa Ayu Dwiyanti (Pusat Riset dan Inovasi Nasional, 2025)
Indonesia is a country that highly upholds the law, this is stated in the 1945 Constitution of the Republic of Indonesia. In line with these provisions, one of the important principles of a state based on law is the guarantee of equality for everyone faced with the law. The emergence of legal disputes related to land begins with objections related to claims for land rights, both regarding land status, priority and ownership, with the hope of obtaining administrative resolution in accordance with applicable provisions. The problem raised in this study is about court decision no. 148 / pdt.g / 2024 / pn in Tabanan. This study uses an empirical legal research method, namely research with field data as the main data source, such as interview results and observations. In addition, this research is also supported by normative data sourced from books and legislative studies. The purpose of this study is In general, this report aims to provide an overview of the settlement of criminal acts of court decisions in Tabanan. Based on the formulation of the problem How is the Implementation of Decision No.148/Pdt.G/2024/PN.Tab Regarding the Validity of Land Ownership Certificates, What legal remedies can be taken by legitimate heirs in the event of cancellation of the transfer of land ownership certificates. The results of the research conducted. It is known that the lack of concreteness of the Tabanan District Court's decision so that the settlement of civil cases is still ongoing, in process or ongoing, so far the parties involved are still trying to find a solution by collecting evidence and witnesses to resolve land disputes in Tabanan, the author concludes that the court has a central role in deciding cases and the author also advises all people before making land purchases and sales to check the completeness of documents, for example certificates.